¿POR QUÉ SHOWMATCH? UN ACERCAMIENTO AL CONSUMO TELEVISIVO DE UNO DE LOS PROGRAMAS MÁS VISTOS EN ARGENTINA - Dra. Yamila Heram, (Fonseca, Journal of Communication, 2023)
Showmatch has remained, almost unchanged, on the screen for more than a decade. It is a beacon product of Argentine air television. Around it organizes and illuminates the rest of the programming, produces ad hoc programs and generates agenda item in the other media. We are interested in the analysis of Showmatch from a double objective.Firstly, realize the characteristics of the program. Secondly, inquire into the forms of consumption and the tastes of the audiences who watch Showmatch.